2021
DOI: 10.3390/ijms22031337
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-Catalyzed 1,4-Dioxane-Mediated Synthesis of Belladine N-Oxides with Anti-Influenza A Virus Activity

Abstract: Belladine N-oxides active against influenza A virus have been synthetized by a novel laccase-catalyzed 1,4-dioxane-mediated oxidation of aromatic and side-chain modified belladine derivatives. Electron paramagnetic resonance (EPR) analysis confirmed the role of 1,4-dioxane as a co-oxidant. The reaction was chemo-selective, showing a high functional-group compatibility. The novel belladine N-oxides were active against influenza A virus, involving the early stage of the virus replication life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The ICW assay was performed using the Odyssey Imaging System (LI-COR, Lincoln, NE, USA) as previously described. 41,42 Briey, A549 cells grown in 96-well plates (2 Â 10 4 cells per well) infected with PR8, and treated or not with high concentrations (100, 150 and 200 mg mL À1 ) of selected compounds were xed with 4% formaldehyde, washed, permeabilized with 0.1% Triton X-100 and incubated with Odyssey Blocking Buffer for 1 h (LI-COR Biosciences, Lincoln, NE, USA). The cells were then stained at 4 C overnight with mouse anti HA (Santa Cruz Biotechnology, Germany) diluted in Odyssey Blocking Buffer.…”
Section: In Cell Western (Icw) Assaymentioning
confidence: 99%
“…The ICW assay was performed using the Odyssey Imaging System (LI-COR, Lincoln, NE, USA) as previously described. 41,42 Briey, A549 cells grown in 96-well plates (2 Â 10 4 cells per well) infected with PR8, and treated or not with high concentrations (100, 150 and 200 mg mL À1 ) of selected compounds were xed with 4% formaldehyde, washed, permeabilized with 0.1% Triton X-100 and incubated with Odyssey Blocking Buffer for 1 h (LI-COR Biosciences, Lincoln, NE, USA). The cells were then stained at 4 C overnight with mouse anti HA (Santa Cruz Biotechnology, Germany) diluted in Odyssey Blocking Buffer.…”
Section: In Cell Western (Icw) Assaymentioning
confidence: 99%
“…Therefore, rats were injected with nonradioactive CS1P1, and plasma was collected at appropriate times to extract Our observation is consistent with literature reports that N-tertiary amines are readily metabolized in vivo into mono-oxidates. 23,31 Together, our data suggested that the molecular structure of major lipophilic radiometabolite observed in human plasma sample is the N-oxide [ 11 C] TZ82121 (Scheme 3).…”
Section: Discussionmentioning
confidence: 68%
“…This and other reactions concerning the MC synthesis of antiviral agents have been recently reported [67]. Due to the increase of in drug-resistance phenomena, as well as novel Influenza virus mutations, novel mechanisms for the inhibition of human influenza virus have been explored [10][11][12][13].…”
Section: Synthesis Of Oseltamivirmentioning
confidence: 98%
“…Recently Quadrelli et al dedicated a chapter of a book to the cycloaddition reactions used for the synthesis of antiviral compounds [7], and a recent review described the biocatalytic routes applied to antiviral agents [8]. Taking into consideration our experience in the antiviral field [9][10][11][12][13][14][15][16][17][18] and in the application of DAR to the synthesis of antiviral agents [15,18] we were interested to investigate this topic in more detail. We show some examples in which the catalytic DARs furnish useful optically active intermediates for the synthesis of selected bioactive compounds after a brief introduction of enantioselective DAR.…”
Section: Introductionmentioning
confidence: 99%